2006
DOI: 10.1007/s10573-006-0072-0
|View full text |Cite
|
Sign up to set email alerts
|

Electromotive force for solid-flame combustion of heterogeneous systems in loose and pressed states

Abstract: By an example of condensed 3Zr + 2WO 3 and Al + Ni systems, it is demonstrated that the electromotive force of solid-flame combustion measured by probing in loose systems is significantly higher than that in the same systems in a pressed state. An explanation for this phenomenon is offered, based on the difference in electrical conductivity in different zones of the combustion wave in loose and pressed condensed systems.Key words: solid-flame combustion, electromotive force of combustion, condensed systems, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In contrast, for electromotive force (EMF) measurements the electrical probes must be situated inside of the reaction zone (area of laser synthesis). In order to reduce parasitic thermo-EMF 13,14 the probe material was chosen to be similar to the synthesized material (hence nickel metal). The thermocouple junctions were located near each probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for electromotive force (EMF) measurements the electrical probes must be situated inside of the reaction zone (area of laser synthesis). In order to reduce parasitic thermo-EMF 13,14 the probe material was chosen to be similar to the synthesized material (hence nickel metal). The thermocouple junctions were located near each probe.…”
Section: Methodsmentioning
confidence: 99%
“…Several experimental studies have revealed that hightemperature front propagation during the combustion synthesis of some compounds generates a voltage of up to 1.5 V. [5][6][7][8][9][10][11][12][13][14] At present the mechanism of these phenomena has not yet been established. Previously we have developed and refined the testing scheme for electro-thermal phenomena studies, which can directly influence the combustion wave front propagation under conditions 15 of SHS-SLS.…”
Section: Introductionmentioning
confidence: 99%